Analisis Tingkat Efisiensi BPRS di Jawa Barat dengan Metode Data Envelopment Analysis (DEA) - Iqlima Yulian Pebrianti (Journal of Applied Islamic Economics and Finance, 2021)
Global Islamic banking has developed rapidly. However, various challenges are still faced by Islamic banking, one of them is efficiency. This study aims to reveal the level efficiency of BPRS and to show the most inefficient variables. This research is quantitative descriptive. The sample is BPRS in West Java. The input variables used in this study: total savings, labor costs, total fixed assets, and capital. The Output is: total financing and other operating income with DEA, VRS model and intermediation approach for the method. The results of this study indicate that BPRS in West Java are still experiencing a fluctuating trend of efficiency and have an average efficiency of 94.52%. This shows that the BPRS in West Java are not yet efficient, but the BPRS in West Java are approaching the point of efficiency and are good enough in carrying out their role as intermediary institutions.